Counseling Anemia in Adolescents Integrated Health Post Teenagers of RT. 06 - Ari Widiana; Yunita, Andri; Martiningsih, Martiningsih; Eriyani, Septi; Santiani, Santiani (Universitas Dehasen Bengkulu, 2025)
One of problem nutrition in adolescents in Indonesia is anemia that still persists be one of problem health the most common society happening in the world, especially in developing countries like Indonesia, anemia happen when level hemoglobin in blood is below normal , so reduce ability blood For transport oxygen to all over body . Deficiency oxygen This can impact on the whole organ function and causes various symptom like weak , tired , lethargic , and difficult concentrate . Among teenagers , in particular teenager daughter , anemia become very important For noticed Because group This currently is in a period of rapid , active growth in a way physical and mental, research This aim For prevent happen his anemia in adolescents in RT 06 Village Like Proceed Subdistrict Puller regency Mukomuko . The method used in the form of counseling to teenager daughter at Posyandu Teenagers Rt 06, with involving 10 KKNT students and midwives Village . Activities covering pre-test , administration material about prevention anemia , examination Hb levels in adolescents daughter , administration of iron tablets , post-test and German exercises . The results of activity This show that understanding to importance prevention anemia in adolescents Still not enough proven with results pre-test which is still low with an average score of 4.4. After given counseling this , level knowledge teenager will prevention anemia increase proven with improved post-test results with an average score of 7.2.